Nuevo varamiento masivo de orca falsa, Pseudorca crassidens, en el Estrecho de Magallanes, Chile - Haro, Daniela; Aguayo Lobo, Anelio; Blank, Olivia; Cifuentes, Constanza; Dougnac, Catherine; Arredondo, Cristóbal; Pardo, Catalina; Cáceres Saez, Iris
We report the mass stranding of 46 false killer whales in the Strait of Magellan in February 2013. We present observation-based information about body size, sex, dental formula and necropsies. Sexual dimorphism in body length was clear, with males being significantly larger than females. Dental formula coincided with previous reports for the species, with asymmetry present in females. Individuals showed normal body conditions without any signs of apparent disease. The cause of the stranding remains unknown, however the coastal morphology hypothesis is a possible explanation. Fil: Haro, Daniela. Universidad de Chile; Chile Fil: Aguayo Lobo, Anelio. Instituto Antártico Chileno; Chile Fil: Blank, Olivia. Clínica Veterinaria Timaukel; Chile Fil: Cifuentes, Constanza. Universidad Mayor; Chile Fil: Dougnac, Catherine. Universidad de Chile; Chile Fil: Arredondo, Cristóbal. Universidad de Chile; Chile Fil: Pardo, Catalina. Universidad de Chile; Chile Fil: Cáceres Saez, Iris. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina